PROFIL PENERBIT NOVEL CHICKLIT DAN TEENLIT INDONESIA - Noor, Redyanto (HUMANIKA, 2014)
Literary works are cultural objects of industrial products. Speaking about the production of literary works meant dealing with laws (systems, mechanisms, and strategies) imposed by the institution concerned-producing, ie the publisher. Therefore, publisher institution (chicklit novel and Teenlit) will create a typical industrial laws, which differ from the laws of other publisher institutions. Systems and mechanisms production of chicklit and Teenlit novel consist of the publisher profile, script acquisition (recruitment), script editing (editing), and script distribution (distribution). Publisher profile includes the publisher history, the publisher specifications and product diversification, as well as the publisher contact. In the modern business communication, publisher identity is as important as product identity. Consumer’s trust is built through the image depiction of products and publisher, thus publisher profile becomes the main reference for consumers. Therefore, in the publisher profile description, it always emphasized its excellence experience (history) in publishing the kind of novel as mentioned before, the specifications and features of products they produce, as well as the tools and the modern systems- mechanisms production (worker qualification, printing machines, management). In relation to the publisher profile, some publishers, Elex Media Komputindo, GagasMedia, and Gramedia Pustaka Utama, have been uniquely designing and presenting (honest, intelligent, and "hanging") and convince the society of readers, especially the readers of Teenlit and chicklit novel.